The impact of the PEPFAR funding freeze on HIV deaths and infections: a mathematical modelling study of seven countries in sub-Saharan Africa - Hontelez, Jan; Goymann, Hannah; Berhane, Yemane; Bhattacharjee, Parinita; Bor, Jacob; Chabata, Sungai T.; Cowan, Frances; Kimani, Joshua; Knox, Justin; Lora, Wezzie S.; Lungu, Cynthia; Manne-Goehler, Jennifer; et al. (EClinicalMedicine, 2025)
Background - On January 24, 2025, the United States government issued an executive order to freeze all foreign aid programs, including The President's Emergency Plan for AIDS Relief (PEPFAR), for 90 days. A limited waiver option became available, but its implementation remains incomplete. We estimated the impact of these policy changes on HIV deaths and new infections in seven sub-Saharan African (SSA) countries—Ethiopia, Kenya, Malawi, South Africa, Tanzania, Zambia, and Zimbabwe -, which together account for about half of all people living with HIV in SSA. - Methods - We used STDSIM, an established individual-based simulation model, and previously published quantifications for the seven countries. We predicted changes in HIV deaths and new infections over the period 2025-2030 for four scenarios: (1) Executive order—proportional, where treatment disruption was proportional to the country-specific PEPFAR's share of total HIV funding; (2) Executive order—realistic, assuming near-total system collapse due to program dependencies; and (3-4) Waiver scenarios where treatment was resumed after 4 or after 8 weeks. Resumptions of programs accounted for delays due to organizational and logistical challenges. - Findings - A 90-day funding freeze would result in 60 thousand [95% UI: 49-71 thousand] excess HIV deaths for the Executive order—proportional scenario. This number would increase to 74 thousand excess HIV deaths [95% UI: 63-89 thousand] for the Executive order—realistic scenario. Under a 4-week and 8-week waiver scenario, projected excess HIV deaths ranged between 21 thousand [95% UI: 15-28 thousand] and 28 thousand [95% UI: 22-36 thousand] respectively. Excess new infections ranged between 35 and 103 thousand for the different scenarios. - Interpretation - The sudden cessation of PEPFAR funding likely results in tens of thousands of HIV deaths and new infections. These losses of life and health should compel the United States government to rapidly and fully re-instate one of the most successful health programs in history. - Funding - None.